Comparison of 3 preventive methods to reduce the recurrence of ankle inversion sprains in male soccer players - Mohammadi, F. (The American Journal of Sports Medicine, 2005)
Background: Ankle sprains are frequent injuries in soccer. Several strategies can be used to prevent further ankle sprains in athletes: the most common are proprioceptive training, strength training, and orthoses.